EVALUATION OF THE CICATRICIAL RESPONSE OF NANOFIBERS LOADED WITH OZONIZED OIL IN DIRECT PULP CAPPING: A CLINICAL CASE REPORT (REMUNOM, 2025)
Background: Direct pulp capping is a conservative procedure that aims to preserve the vitality of the dental pulp after exposure. Recent advances have explored the use of nanofibers loaded with ozonized oil for their regenerative and antimicrobial properties. Objectives: To report the clinical use of a nanofiber impregnated with ozonized sunflower oil as a direct pulp capping material, assessing clinical and radiographic responses and the impact on the patient’s quality of life. Case report: A clinical case was documented involving a 40-year-old female patient with reversible pulpitis in the lower right first molar. After controlled pulp exposure, the site was treated with nanofibers impregnated with ozonized sunflower oil and sealed with a bioactive adhesive system. Clinical and radiographic evaluations were performed at 7, 14, and 30 days, along with pain assessment using the Visual Analog Scale (VAS) and the OHIP-14 questionnaire to measure quality of life. Results: The patient experienced complete pain remission within 30 days, with restoration of normal pulp sensitivity and absence of periapical changes on radiographs. Clinical signs suggested pulp tissue repair, and the patient reported a marked improvement in oral health-related quality of life. Conclusions: The use of ozonized oil-loaded nanofibers as a direct pulp capping material showed favorable clinical outcomes and may represent a promising approach. However, further clinical studies are required to validate these preliminary findings.